Finding Nemo (New York, 2003)
When a young clown fish, Nemo, is captured and put into a fish tank, his father and his new friend, Dory, set out to rescue him and bring him home. While his father is looking for him, Nemo is planning a scheme to escape and return to the sea.
Keywords: Juvenile fiction; (Fictitious character); Nemo; Finding Nemo (Motion picture); Juvenile fiction; Fishes; Juvenile fiction; Nemo (Fictitious character); Juvenile fiction; Ocean; Action and adventure fiction; Picture books